Audit on Current Practice of Rapid Sequence Induction and Intubation of Anesthesia in the University of Gondar Hospital, Northwest Ethiopia, 2018. (22nd September 2019) - Mollalign, Mamaru; Gebreegzi, Amare Hailekiros; Getinet, Habtamu; Adem, Seid
Abstract : Background . In patients who are liable to the risk of pulmonary aspiration, airway control is the primary and first concern for the anesthetists both in emergency and elective surgical procedures. Rapid sequence induction is universally required in any occasion of emergent endotracheal intubation needed for unfasted patients or patients' fasting status is unknown. Methods . institutional-based prospective observational study was conducted from December 2017 to January 2018 in all elective and emergency adult or pediatric patients with a risk of pulmonary aspiration who were operated under general anesthesia with rapid sequence induction and intubation during the audit period. Result . A total of 35 patients were operated during the study period. Of these, 31 (88.57%) patients were adults and 4 (11.43%) patients were pediatrics. Most of the patients were emergency (29 (82.857%)), and the rest were elective (6 (17.142%)). Conclusion . Most anesthetists were good at preparing all available monitoring and drugs, making sure that IV line is well-functioning, preparing suction with a suction machine, preoxygenation, application of cricoid pressure, and checking the position of the ETT after intubation was performed. Preparing difficult airway equipment during planning of rapid sequence induction and intubation, giving roles and told to proceed their assigned role for the team, attempt to ventilate with a small tidal volume, and routine use of bougie or stylet to increase the chance of success of intubation needed improvement.